IL-37 counteracts inflammatory injury in the temporomandibular joint via the intracellular pathway - Li, Jun; Peng, Sisi; Yan, Ying; Yan, Shan; Cao, Xin; Li, Yong; Zhu, Luying; Xu, Jie (Frontiers in Pharmacology, 2023)
The temporomandibular joint (TMJ) is often afflicted by osteoarthritis (TMJOA), causing pain and dysfunction, which is particularly prevalent in the elderly population. IL-37 is effective in avoiding excessive inflammatory damage to the organism. This article investigates the role and mechanism of intracellular IL-37 in TMJOA.Methods: ELISA, quantitative real-time polymerase chain reaction, western blotting, Senescence-associated β-galactosidase staining, immunofluorescence, and lentivirus were performed to elucidate the underlying mechanism.The results confirmed that IL-37 in synovial cells decreased with aging. Inflammatory stimulus elevated intracellular IL-37 in synoviocytes, while lentiviral knockdown of IL-37 resulted in more inflammatory factor production. Dynamic changes of IL-37 were observed in the nucleus and supernatant. In addition, Caspease-1 inhibitor hindered intracellular IL-37 maturation, and Smad3 inhibitor caused the loss of nuclear translocation of mature IL-37. Transfection of synovial cells with IL-37expressing lentivirus resulted in relief not only of synovitis but also of the cartilage damage and inflammation caused by synovitis.This study provides new insights into the intracellular anti-inflammatory mechanism of IL-37. It also confirms that IL-37 decreases with cellular senescence and that increasing intracellular IL-37 can effectively treat synovitis and synovitis-induced inflammatory damage to cartilage.